2016
DOI: 10.1007/s11605-015-2956-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Gastrointestinal Telemetry with an Acoustic Biosensor Predicts Ileus vs. Uneventful GI Recovery

Abstract: Non-invasive, abdominal, acoustic monitoring prospectively predicts POI. Surgeons may use AGIS to rule out POI with over 80% certainty; this offers added confidence to advance feeding earlier in those for whom it is safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…115 Emerging non-invasive biosensor technology such as acoustic GI surveillance and bedside ultrasound have shown promise in measuring gut motility within small case series following surgery. 116,117 These studies, although interesting, will need multi-institutional validation prior to incorporation into clinical practice.…”
Section: Question #2mentioning
confidence: 99%
“…115 Emerging non-invasive biosensor technology such as acoustic GI surveillance and bedside ultrasound have shown promise in measuring gut motility within small case series following surgery. 116,117 These studies, although interesting, will need multi-institutional validation prior to incorporation into clinical practice.…”
Section: Question #2mentioning
confidence: 99%
“…The clinical relevance of this proof of principle study relates to the impact of assessing motility in horses with gastrointestinal disorders, particularly post-operative ileus (POI). Kaneshiro et al recently showed that AGIS biosensors predicted POI onset in humans following colorectal surgery with a sensitivity of 63%, specificity of 72%, and NPV of 81%, allowing surgeons to rule out POI with over 80% confidence [20]. If this can also be validated in the horse, AGIS biosensors may become an invaluable monitoring tool to evaluate gastrointestinal motility and guide postoperative management by providing continuous gastrointestinal monitoring that can be used to objectively quantify motility.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the current study of BSs, there is no recognized gold standard for the recognition accuracy of EBSs, and there is no standardized database to verify the accuracy. Most of the reference standards in the current study are based on the subjective judgment of clinicians, but the accuracy of such subjective judgment is also questionable [8]. Future research might use the device we made to test BSs at different intervals post operation to determine the time it takes for intestinal function to return to pre-op status in individuals to more accurately judge the optimal post operation feeding times.…”
Section: Discussionmentioning
confidence: 99%
“…However, using a handheld stethoscope for auscultation is still the main way to quickly obtain intestinal sounds in the clinic. As for the identifying the speci c gut sounds, the results tend to be random and depend on of subjective judgment and are therefore questionable [8,9]. In the study of BSs, the sounds are acquired by means of an assembly of mature pickups and storage units.…”
Section: Studies Of Noninvasive Methods To Judge the Recovery Of Gastmentioning
confidence: 99%